Safety of endoscopist-guided sedation in a low-risk collective: a randomised multicentre study (Prosed3 study): Originalarbeit - Behrens, Angelika; Ell, Christian; Frieling, Thomas; Labenz, Joachim; May, Andrea; Ellrichmann, Mark; Schilling, Dieter; Kreuzmayr, Anton; Schmitz, Volker; Ballmann, Clemens; von Tirpitz, Christian; Schäfer, Claus; et al. (Zeitschrift für Gastroenterologie, 2023)
Introduction: Worldwide, gastrointestinal endoscopies are predominantly performed under sedation. National and international guidelines and recommendations contain very different specifications for the use of sedation in gastrointestinal endoscopy. These differences come from specific requirements for staffing during endoscopy. Aim: The aim of the study is to evaluate whether endoscopist-guided sedation without additional sedation assistance is not inferior to endoscopist-guided sedation with additional sedation assistance with respect to the rate of sedation-associated complications in a defined low-risk population (low-risk procedure and low-risk patient). Methods: Prospective, multicenter, randomized study. Results: 27 German study centers participated in the study. A total of 30 569 endoscopies were recorded during the study period from 1.8.2015 to 10.3.2020. The final data analysis included 28 673 examinations (64.1 % esophagosgastroduodenoscopies and 35.9 % colonoscopies). In 307 (1.1 %) examinations, 322 sedation-associated complications occurred. Of these, 321 (1.1 %) were minor complications and one (0.003 %) was a major complication. There was no statistically significant difference in the frequency of sedation-associated complications between endoscopist-guided sedation with versus without additional sedation assistance. Within the legal framework, a “shadow” sedation assistant was present in the study group without sedation assistance. This assistant intervened because of sedation-associated complications in 101 (0.7 %) of the endoscopies. Conclusion:The study documents the safety of propofol-based endoscopist-guided sedation in a low-risk population. In 98.9 % of all endoscopies, no sedation-associated complication occurred or it was so minimal that no intervention (e. g., increase of oxygen supply) was necessary. The study cannot answer to what extent a serious complication was avoided by the active intervention of the “shadow” sedation assistance in the group without sedation assistance. The study proves in a randomized, prospective design that sedation in low-risk endoscopy (low-risk patient, low-risk procedure) can be performed as endoscopist-guided sedation without additional sedation assistance, without demonstrably accepting a reduction in safety.